2004
DOI: 10.1109/jsen.2004.836849
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Single-Chip pH Sensor Using a Conventional 0.6-<tex>$muhbox m$</tex>CMOS Process

Abstract: Abstract-A pH sensor fabricated on a single chip by an unmodified, commercial 0.6-m CMOS process is presented. The sensor comprises a circuit for making differential measurements between an ion-sensitive field-effect transistor (ISFET) and a reference FET (REFET). The ISFET has a floating-gate structure and uses the silicon nitride passivation layer as a pH-sensitive insulator. As fabricated, it has a large threshold voltage that is postulated to be caused by a trapped charge on the floating gate. Ultraviolet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(43 citation statements)
references
References 18 publications
(22 reference statements)
0
43
0
Order By: Relevance
“…The methodology used to design the ISFETs is adopted by Hammond et al [3] where by the polysilicon gate is connected via the metal layers to the top metal layer covered by silicon nitride passivation. This is left floating to be biased by an external reference electrode.…”
Section: Isfet Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology used to design the ISFETs is adopted by Hammond et al [3] where by the polysilicon gate is connected via the metal layers to the top metal layer covered by silicon nitride passivation. This is left floating to be biased by an external reference electrode.…”
Section: Isfet Fabricationmentioning
confidence: 99%
“…ISFET (Ion Sensitive Field Effect Transistor) based chemical sensors, first introduced by Bergveld [2], have gained considerable interest due to their ion sensitivity, fast temporal response, compact size and prospect of monolithic integration [3]. Although much of the initial literature predicted ISFETs to be mainly used as future tools for electrophysiological measurements, the sensors were not further developed for biomedical applications in particular, but rather for ion sensing in general [2].…”
Section: Introductionmentioning
confidence: 99%
“…7. The properties of an ISFET fabricated using this method have been described elsewhere [9]. The ISFET2_CIRCUIT block (Fig.…”
Section: B the Analogue Subsystemmentioning
confidence: 99%
“…Recently, ISFETs have been fabricated in an unmodified commercial process, but were found to suffer from large and unpredictable threshold voltages [8]. This problem has been attributed to trapped charge, which can be removed using ultra-violet radiation [9]. In this paper, the idea of the CMOS ISFET is extended to a complete system-on-chip digital pH meter, ideal for use in a capsule-based diagnostic device, but with many other potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is similar to the trapped charges found in the gate oxide of MOSFETs. In an extreme case, Hammond et al reported that their p-typed ISFETs had threshold voltages of 5 V [9]. This is a big problem in biasing the ISFETs under a 3.3 V power supply.…”
mentioning
confidence: 99%